Fixed Point Theorems for Operators with Certain Condition in p-Uniformly Convex Metric Spaces. (22nd November 2022) - Knefati, Mohammad; Karakaya, Vatan
Abstract: In this paper, firstly, we extend the nonlinear Lebesgue spaces from the setting of Hadamard spaces to the setting of p -uniformly convex metric spaces. Afterward, we establish some Δ-convergence and strong convergence theorems for a recently introduced class of generalized nonexpansive mappings in the setting of p -uniformly convex metric spaces. Furthermore, we employ the newly introduced JK -iteration process to approximate the fixed points of this class. Finally, we construct new examples of this class of mappings in the context of p -uniformly convex metric spaces.